Correction of sagittal imbalance in treatment for adult degenerative scoliosis with thoracic lordosis and lumbar kyphosis: A case report. Issue 16 (April 2017) - Wang, Tao; Wang, Hui; Ma, Lei; Zhang, Di; Ding, Wen-Yuan
Abstract: Rationale: Lumbar degenerative scoliosis (LDS) is a common spinal disease for senior citizens. However, LDS accompanied with thoracic lordosis and lumbar kyphosis (LK) is rare in clinic. No reports have reported LDS with thoracic lordosis and LK. Patient concerns: A 54-year-old woman just complained about sever back pain without any radiculopathy and neurodeficit of low limb for 2 years, Visual Analogue Scale (VAS) for back pain was 9 points and x-ray showed adult LDS with lordosis angle of 10° from 5th thoracic to 12th thoracic (T5-T12) and LK angle of 20°. Diagnoses: She was diagnosed with adult degeneration scoliosis (ADS). Interventions: : The patient underwent posterior pedicle screw implantation from L1 to S1 levels. Outcomes: : Two weeks after surgery, VAS for back pain was 2 points and x-ray showed thoracic lordosis angle of 6°, lumbar lordosis (LL) of 6° and sagittal vertical axis from C7 plumb line (SVA) of 77 mm. One year after surgery, VAS for back pain was 1 points and the x-ray showed thoracic lordosis angle of 6°, LL of 20°, and SVA of 36 mm, implying globe spine for this patient tends to balance. Lessons: Adult degenerative scoliosis accompanied with thoracic lordosis and LK is rare. Correcting sagittal imbalance is an effective treatment. The surgical outcome is satisfactory. Attention should be paid in sagittal balance for treatment of ADS. We still need further follow-up to observe change of sagittal parameters.